Severe Cases of Tick-Borne Encephalitis in Northeastern Poland - Justyna Adamczuk; Magdalena Chlabicz; Natalia Koda; Maciej Kondrusik; Joanna Zajkowska; Piotr Czupryna; Anna Moniuszko-Malinowska (Pathogens)
Tick-borne encephalitis (TBE) is the most prevalent viral infection of the central nervous system (CNS) in Poland. The disease is characterized by the presence of two stages. The first phase, called the viremic stage, presents with flu-like symptoms, while the second stage of TBE is characterized by damage to the nervous system and may follow a severe and dramatic course. The aim of this paper is to increase the awareness of the potential sequelae after TBE. In this study, we report cases of severe TBE in 36-year-old and 57-year-old female patients. The outcome of TBE varies from patient to patient, but there are some factors that can help to predict the severity of TBE infection. The risk factors presented in these patients were as follows: the monophasic course of TBE, high pleocytosis in cerebrospinal fluid (CSF) and older age. Both of our patients were not vaccinated despite the World Health Organization’s (WHO’s) recommendations. Both patients had no history of travel outside their region of residence prior to the onset of illness. The few risk factors shown in our patients and the serious sequelae of the disease may indicate the need to test patients for possible gene mutations.